Carbon quantum dot taking orange peel as carbon source as well as preparation method and application of carbon quantum dot

By using the orange-made carbon quantum dot (OP-CQDS), the lack of detection of FE3+and L-anti-hemorrhohic acid in the existing technologies to achieve high selective, fast and simple dual detection capabilities, and they have a wide range Application prospects.

CN119349558AActive Publication Date: 2025-01-24HUAQIAO UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411919779.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

There is a lack of fluorescence sensors that can detect Fe3+ and L-ascorbic acid (L-AA) simply, quickly and accurately.

Method used

By using orange skin as a carbon source, a carbon quantum dot (OP-CQDS) is prepared. The carbon quantum dot has strong fluorescent characteristics and can highly selectively detect Fe3+and L-AA.

Benefits of technology

The carbon quantum dot fluorescent probe can not only quickly and simply detect Fe3+and L-AA, but also shows excellent performance stability and extensive application prospects, especially in the field of biochemistry analysis and environmental monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349558A_ABST
    Figure CN119349558A_ABST
Patent Text Reader

Abstract

The invention provides a carbon quantum dot taking orange peel as a carbon source as well as a preparation method and application of the carbon quantum dot, and belongs to the technical field of testing or analyzing materials by means of measuring chemical or physical properties of the materials. The preparation method comprises the following steps: cleaning and drying orange peel to prepare orange peel powder, mixing the orange peel powder with distilled water, performing hydrothermal reaction, cooling to room temperature, and filtering to obtain the carbon quantum dots; the ratio of the orange peel powder to the distilled water is 0.5 g: (20-30) ml; the temperature of the hydrothermal reaction is 190-210 DEG C, and the heat preservation time is 5-7 hours. The preparation method of the carbon quantum dots is simple, green, environment-friendly and non-toxic. The carbon quantum dot fluorescent probe not only can detect Fe < 3 + > with high selectivity, but also can continuously detect L-AA with high selectivity on the basis of detecting Fe < 3 + >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon quantum dot using orange peel as a carbon source and a preparation method and application thereof, belonging to the technical field of testing or analyzing materials by measuring the chemical or physical properties of the materials, in particular to detecting Fe 3+ And the technical field of preparation of carbon quantum of L-AA. Background Art

[0002] Iron is an indispensable trace element in living organisms. 3+ It plays a vital role in maintaining the balance of cell systems. 3+ Imbalance may damage the cell system and lead to a series of diseases, such as Alzheimer's disease, heart failure, metabolic disorders and Parkinson's disease. L-Ascorbic acid (L-AA), commonly known as vitamin C, is an essential food-derived nutrient for the human body. It has antioxidant properties and plays an important role in metabolism and immune system function.

[0003] L-AA is the abbreviation of L-Ascorbicacid, also known as L-ascorbic acid or vitamin C. It is a water-soluble compound that is widely found in fresh vegetables and fruits, especially citrus fruits. L-AA plays important roles in the human body, including acting as an antioxidant, promoting collagen deposition, inhibiting elasticity production, anti-cancer effects, and stimulating immune responses. Since the human body cannot synthesize L-AA on its own, it must be met through dietary intake. Lack of L-AA can lead to scurvy, which manifests as symptoms such as brown spots on the skin, spongy gums, and mucous membrane bleeding. In the cosmetics industry, L-AA is also used as an antioxidant and pH adjuster. In addition, L-AA is also used as a food additive, which has the function of preservation and nutritional supplement.

[0004] Currently, Fe 3+ The main methods for detecting L-AA include electrochemical analysis, chromatography, colorimetry, mass spectrometry and fluorescence analysis. Large-scale instrument testing has problems such as high cost and complicated sample pretreatment procedures, while fluorescence analysis has good application prospects due to its simple operation, high detection sensitivity and low time consumption. 3+ Given the important roles of L-AA and L-AA in human health, it is of great significance to develop a fluorescent sensor that can detect these two substances simply, quickly and accurately.

[0005] Carbon quantum dots (CQDs) are a type of carbon nanomaterial with significant fluorescence properties. They are composed of nearly spherical, dispersed carbon nanoparticles with a diameter of less than 10 nm. CQDs have a large specific surface area and rich functional groups, which are conducive to interaction with other substances. They show excellent fluorescence properties, good water solubility, low toxicity, biocompatibility and chemical stability. They are an excellent fluorescent probe. As a fluorescent probe, CQDs have the advantages of being fast, simple, selective, highly sensitive, and having a wide and continuous excitation spectrum. They have been widely used in many fields such as food safety, metal ion detection, environmental monitoring and cell imaging.

[0006] However, there is no Fe that can be detected in the prior art. 3+ and carbon quantum dots of L-AA. Summary of the invention

[0007] The present invention provides a carbon quantum dot using orange peel as a carbon source and a preparation method and application thereof, which can effectively solve the above problems.

[0008] The present invention is achieved in that: A method for preparing carbon quantum dots using orange peel as a carbon source comprises the following steps: washing and drying the orange peel to prepare orange peel powder, mixing the orange peel powder with distilled water, performing a hydrothermal reaction, cooling to room temperature, and filtering to obtain carbon quantum dots; the ratio of the orange peel powder to the distilled water is 0.5 g: 20-30 ml; the temperature of the hydrothermal reaction is 190-210° C., and the insulation time is 5-7 hours.

[0009] In some embodiments, the drying temperature is 80-100° C. and the drying time is 2-3 days.

[0010] In some embodiments, the filtering is filtering through a 0.22 μm microporous membrane.

[0011] A carbon quantum dot prepared by the method using orange peel as a carbon source.

[0012] In some embodiments, the particle size of the carbon quantum dots is 2.2-6.2 nm.

[0013] A method for detecting iron ions comprises mixing the carbon quantum dots with a solution containing iron ions, measuring the fluorescence spectrum intensity after sufficient reaction, and calculating the concentration of the iron ions according to the change of the fluorescence spectrum intensity.

[0014] In some embodiments, the excitation wavelength of the fluorescence spectrum is 355-365 nm.

[0015] In some embodiments, the detection range of iron ions is 0-90 μmol·L -1 A method for detecting L-ascorbic acid comprises mixing the carbon quantum dots with a solution containing iron ions, measuring the fluorescence spectrum after sufficient reaction, adding a solution containing L-ascorbic acid after fluorescence quenching, measuring the fluorescence spectrum again, and calculating the concentration of L-ascorbic acid according to the degree of recovery of fluorescence intensity.

[0016] In some embodiments, the detection range of L-ascorbic acid is 0-2000 μmol·L -1 .

[0017] The beneficial effects of the present invention are: The present invention relates to a method for preparing carbon quantum dots using orange peel as a carbon source. This method is not only simple and easy to implement, but also has the characteristics of being green, environmentally friendly and non-toxic. The prepared carbon quantum dots have good solubility in water and exhibit strong fluorescence characteristics. In addition, these carbon quantum dots exhibit excellent performance stability within the physiological pH range. More importantly, these carbon quantum dots can be used as fluorescent probes, which can not only detect Fe 3+ ions, and in completing Fe 3+ On the basis of detection, it can also continuously and highly selectively detect L-ascorbic acid (L-AA). This dual detection capability makes the carbon quantum dot fluorescent probe have broad application prospects in the fields of biochemical analysis and environmental monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The morphology and structure characterization of the OP-CQDs of Example 2, wherein a is the TEM image of the OP-CQDs; and b is the particle size distribution diagram of the OP-CQDs.

[0020] Figure 2 Fluorescence excitation and emission spectra of OP-CQDs.

[0021] Figure 3 The selectivity of OP-CQDs in detecting metal ions, where a is the fluorescence spectra of OP-CQDs at the same concentration of different metal ions; b is the fluorescence response diagram of OP-CQDs at the same concentration of different metal ions at an emission wavelength of 445 nm.

[0022] Figure 4 is the Fe 3+Detection specificity, where a is the concentration of Fe 3+ Fluorescence spectra of OP-CQDs under 3+ The concentration is between 10 and 60 μmol·L -1 The fluorescence intensity changes in the range are linearly related to the concentration (emission wavelength is 445 nm).

[0023] Figure 5 is the detection of L-AA by OP-CQDs, where a is the OP-CQDs-Fe 3+ Fluorescence spectra of the solutions; b is the fluorescence spectra of L-AA concentrations in the range of 0 to 2000 μmol·L -1 Fluorescence intensity changes with concentration in the range of 5~300μmol·L -1 The fluorescence intensity changes in the range are linearly related to the concentration. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Embodiments of the present invention relate to an innovative preparation method that uses orange peel as a carbon source to synthesize carbon quantum dots. Specifically, the present invention provides a simple and efficient technology that finally obtains carbon quantum dots with specific properties, namely OP-CQDs, by subjecting orange peels to a series of processing steps. First, the orange peels are thoroughly cleaned and then dried to remove excess water and impurities. The dried orange peels are further ground into a powder to form orange peel powder.

[0026] Next, the prepared orange peel powder is mixed with distilled water in a certain ratio. In the present invention, the ratio of orange peel powder to distilled water is designed to be 0.5 grams of orange peel powder corresponding to 20 to 30 milliliters of distilled water. This ratio is selected to ensure that the orange peel powder can be fully dissolved and reacted in the subsequent hydrothermal reaction, thereby effectively generating the desired carbon quantum dots.

[0027] The mixed solution is then placed in a closed reaction vessel for a hydrothermal reaction. A hydrothermal reaction is a chemical reaction carried out under high temperature and high pressure conditions that can promote the transformation between substances and the generation of new substances. In the present invention, the temperature of the hydrothermal reaction is set between 190 and 210 degrees Celsius, which can ensure the smooth progress of the reaction while avoiding side reactions or decomposition of carbon quantum dots caused by excessively high temperatures. In addition, the holding time of the hydrothermal reaction is set to 5 to 7 hours, which is a length of time to ensure that the carbon source in the orange peel powder can fully react to generate high-quality carbon quantum dots.

[0028] After the hydrothermal reaction, the reaction mixture needs to be cooled to room temperature. The cooling process is carried out slowly to prevent the carbon quantum dots from agglomerating or structurally destroying due to a sudden drop in temperature. After the cooling is completed, the unreacted solid impurities are removed by a filtration step to obtain a pure carbon quantum dot solution. Finally, a pure carbon quantum dot product, i.e., OP-CQDs, can be obtained through appropriate post-processing steps such as centrifugation, washing, and drying.

[0029] In summary, the present invention provides a method for preparing carbon quantum dots using orange peel as a carbon source, which is not only environmentally friendly but also low in cost and has high practical value and application prospects. The carbon quantum dots prepared by this method have broad application potential in the fields of optoelectronics, bioimaging, sensors, etc.

[0030] In some embodiments, the drying temperature is 80-100° C. and the drying time is 2-3 days.

[0031] In some specific embodiments, the filtration process is performed by using a 0.22 micron microporous membrane to ensure that impurities and particles in the solution are effectively removed.

[0032] The present invention provides a carbon quantum dot prepared by the above specific method, wherein the carbon source is mainly derived from orange peel. In this process, the orange peel undergoes a series of chemical reactions and processing steps and is ultimately converted into carbon quantum dots with unique properties. These carbon quantum dots exhibit excellent performance and characteristics in certain embodiments.

[0033] In these embodiments, the prepared carbon quantum dots have a specific particle size range between 2.2 nanometers and 6.2 nanometers. This particle size range makes these carbon quantum dots perform well in optical, electronic and chemical applications. Due to their tiny size, these carbon quantum dots have a high surface area to volume ratio, thus having broad application prospects in catalysis, sensors and bioimaging. In addition, the carbon quantum dots made from orange peels are not only environmentally friendly, but also cost-effective, providing new ideas for sustainable development.

[0034] Embodiments of the present invention provide a method for detecting the concentration of iron ions. Specifically, the method involves mixing carbon quantum dots with a solution containing iron ions. After mixing, the mixture is allowed to fully react for a period of time to ensure that the reaction is completely carried out. After the reaction is completed, further analysis is performed by measuring the fluorescence spectrum intensity of the mixed solution. By analyzing the changes in the fluorescence spectrum intensity, the specific concentration of iron ions in the solution can be calculated.

[0035] The detailed explanation of the detection mechanism of iron ion concentration is as follows: On the surface of OP-CQDs, there are a large number of active groups such as hydroxyl, amino and carboxyl. These groups play a key role on the surface of OP-CQDs. Specifically, these groups may interact with Fe through electronic transitions. 3+ The d orbitals of ions interact with each other. This interaction leads to the 3+ Chelation between ions. Chelation is a special chemical reaction in which a molecule or ion binds to a central metal ion through multiple coordination bonds to form a ring structure. In this process, the fluorescence properties of OP-CQDs may be suppressed. In other words, when Fe 3+ When ions chelate with the active groups on the surface of OP-CQDs, this binding interferes with the electronic transition process of OP-CQDs, causing its fluorescence intensity to weaken or disappear. This phenomenon can be used to detect Fe 3+ The presence and concentration of ions.

[0036] In some specific embodiments, in order to obtain the best detection effect, the excitation wavelength of the fluorescence spectrum is set between 355 and 365 nanometers. By selecting this specific wavelength range, the intensity and stability of the fluorescence signal can be ensured, thereby improving the accuracy and reliability of the detection.

[0037] In addition, in some embodiments, the detection method can cover the iron ion concentration range of 0 to 90 μmol·L -1 ). This means that this method can not only detect low concentrations of iron ions, but also be applicable to the detection of iron ions in a higher concentration range, thus having a wider range of applications and higher practicality. Through this method, accurate quantitative analysis of iron ions of different concentrations can be conveniently performed.

[0038] An embodiment of the present invention provides a method for detecting the content of L-ascorbic acid (vitamin C). The method involves mixing carbon quantum dots with a solution containing iron ions and ensuring that a sufficient chemical reaction occurs between the two. After the reaction is completed, the reaction is evaluated by measuring the fluorescence spectrum of the mixed solution. Specifically, when a significant decrease or quenching of the fluorescence intensity is observed, it indicates that a certain complex has been formed between the carbon quantum dots and the iron ions.

[0039] Next, add the sample solution containing L-ascorbic acid to the mixed solution. L-ascorbic acid reacts with iron ions, thereby affecting the stability of the carbon quantum dots and iron ion complex. By measuring the fluorescence spectrum again, the change in fluorescence intensity can be observed. If the fluorescence intensity is restored, it indicates that the presence of L-ascorbic acid causes the iron ions to be released from the complex.

[0040] According to the degree of fluorescence intensity recovery, the concentration of L-ascorbic acid can be quantitatively calculated. In some specific embodiments, the detection method can cover the range from 0 to 2000 μmol·L -1 ). This method can accurately determine the content of L-ascorbic acid in samples, thus providing an effective detection method for food, medicine and biological sample analysis.

[0041] The detailed description of the detection mechanism of L-ascorbic acid (vitamin C) content is as follows: 3+ In the system, when L-AA (L-ascorbic acid) is added, L-AA will react with Fe 3+ A redox reaction occurs. In this process, L-AA acts as a reducing agent to reduce Fe 3+ Reduction to Fe 2+ , and L-AA itself is oxidized. 3+ The decrease in the amount of L-AA caused the interaction between OP-CQDs (graphene oxide quantum dots) that originally interacted with it to be destroyed. The destruction of this interaction led to the recovery of some of the suppressed fluorescence signals in the system. Therefore, by monitoring the changes in the fluorescence intensity of the system, the concentration of L-AA can be indirectly reflected, thereby achieving quantitative detection of L-AA. This process not only reveals the interaction between OP-CQDs and Fe 3+ The interaction mechanism between them is also shown, and the potential of using this interaction change to detect specific substances is demonstrated.

[0042] Example 1: A method for preparing carbon quantum dots using orange peel as a carbon source First, fresh Gannan navel orange peels were selected, placed in a beaker, and thoroughly washed with distilled water. After washing, the orange peels were torn into small pieces and placed in a 90°C oven for 2.5 days of drying. After drying, the orange peel pieces were placed in a mortar and ground into fine powder.

[0043] Next, 0.5 g of the orange peel powder was weighed and mixed with 30 ml of distilled water to ensure uniform mixing. The mixture was placed in an electric heating blast drying oven and reacted at 200° C. for 6 hours.

[0044] After the reaction is completed, the reactor is cooled to room temperature naturally, and the residue is first removed by room temperature filtration, followed by secondary filtration using a 0.22-micron microporous filter membrane to obtain a clear orange-yellow OP-CQDs stock solution. Finally, the stock solution is diluted 20 times and used as the working solution for subsequent experiments.

[0045] Example 2: Characterization and analysis of OP-CQDs The morphological characteristics of blue fluorescent carbon dots from roxburghii were carefully characterized by transmission electron microscopy (TEM). Figure 1 Figure a shows the TEM image of OP-CQDs prepared in Example 1. It can be observed from the figure that OP-CQDs have good dispersion and present a regular spherical structure. The lattice spacing shown in the inset is 0.27 nanometers, which is highly consistent with the (002) crystal plane of graphite, further confirming that the synthesized OP-CQDs belong to the category of carbon quantum dots (CQDs).

[0046] Figure 2 The fluorescence excitation and emission spectra of OP-CQDs are shown. It can be clearly seen from the figure that when the excitation wavelength is 360 nanometers, OP-CQDs exhibit the strongest fluorescence intensity at the maximum emission wavelength of about 445 nanometers.

[0047] Example 3 Application of OP-CQDs as a fluorescent probe in detecting iron ions Add 2 mL of OP-CQDs working solution to the cuvette and 1 mL of 10 mmol·L -1 14 different metal ion aqueous solutions (Mn 2+ 、Cd 2+ 、Co 2+ 、Ce 2+ 、Zn 2+ , Cu 2+ Mg 2+ , Fe 2+ , Fe 3+ 、Ag+、Ni 2+ , Pb 2+ , Ba 2+ and Ca 2 + ), after fully reacting for about 15 minutes, the fluorescence spectrum of each solution was measured (excitation wavelength was 360 nm).

[0048] Selectivity is an important indicator for evaluating the performance of fluorescent probes. Fourteen metal ions were selected as interfering ions and added into the OP-CQDs working solution to investigate the changes in the fluorescence properties of OP-CQDs. Figure 3As shown in the figure, after adding equal amounts of different metal ions to OP-CQDs, the peak shape of the fluorescence spectrum did not change significantly, and the intensity changed slightly. 3+ When the fluorescence of OP-CQDs is almost completely quenched, it indicates that OP-CQDs have a strong affinity for Fe 3+ Has good selectivity.

[0049] 3 mL of OP-CQDs working solution was mixed with different volumes of 2 mmol·L -1 Fe 3+ Mixing makes Fe 3+ The concentration range is 0~90μmol·L -1 , and investigate the changes in its fluorescence spectrum.

[0050] Figure 4 The OP-CQDs were shown to be effective for Fe 3+ The sensitivity test results. Figure 4 It can be observed that in Fe 3+ Concentration ranged from 0 to 90 μmol·L -1 In the range of Fe 3+ As the concentration gradually increases, the fluorescence intensity of OP-CQDs shows a trend of gradually weakening. Figure 4 In b, we found that at an emission wavelength of 445 nm, the change in fluorescence intensity (F0-F) was related to Fe 3+ The concentration ranged from 10 to 60 μmol·L -1 There is a significant linear correlation in the range of .

[0051] According to the calculation formula of detection limit LOD=3σ / k (where σ represents the standard deviation of the blank sample and k is the slope of the linear equation), we can get Fe 3+ The detection limit was 1.1 μmol·L -1 This value is significantly lower than the recommended level of Fe in drinking water set by the World Health Organization. 3+ The maximum limit standard (5.36 μmol·L -1 ), thus proving that the synthesized OP-CQDs 3+ Excellent sensitivity in detection.

[0052] Example 4 Application of OP-CQDs as fluorescent probes in detecting iron ions and L-ascorbic acid 2 mL of OP-CQDs working solution was mixed with 10 μL of 1 mol·L -1 Fe 3+ The aqueous solution was mixed to prepare OP-CQDs-Fe 3+ Add 10 mL of solution and mix thoroughly.

[0053] Take out 2mL OP-CQDs-Fe 3+ The solution was placed in a cuvette and different volumes of 1, 10 and 50 mmol·L - 1 L-AA, so that the concentration range of L-AA is 0~2000μmol·L -1 , investigate OP-CQDs-Fe 3+ Changes in fluorescence spectra.

[0054] In Fe 3+ After quenching the fluorescence of the OP-CQDs system, different concentrations of L-AA were added to the system, and it was found that L-AA could make the OP-CQDs-Fe 3+ The fluorescence of the system was partially restored.

[0055] like Figure 5 As shown in a, when the L-AA (ascorbic acid) concentration ranged from 0 to 2000 μmol·L -1 In the range of , it can be observed that with the gradual increase of L-AA concentration, the fluorescence intensity shows a trend of gradual enhancement. Figure 5 Figure b shows the relationship between the fluorescence intensity change (F-F0) and the L-AA concentration at an emission wavelength of 445 nm. 3+ The fluorescence intensity change of the system showed a significant exponential function relationship with the concentration of L-AA. This phenomenon may be attributed to the effect of L-AA on Fe 3+ The reduction of Fe 3+ Converted to Fe 2+ , thereby reducing the OP-CQDs-Fe 3+ The energy transfer and electron transfer efficiency within the system lead to partial recovery of fluorescence.

[0056] Further observation Figure 5 c, when the L-AA concentration was 50 to 600 μmol·L -1 In the range of 445 nm, the fluorescence intensity change (F-F0) at the emission wavelength of 445 nm showed a linear relationship with the L-AA concentration. According to the calculation formula of the detection limit LOD=3σ / k (where σ represents the standard deviation of the blank sample and k is the slope of the linear equation), it can be concluded that the detection limit of L-AA is 32 μmol·L -1 .

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing carbon quantum dots using orange peel as a carbon source, characterized in that: The orange peel is washed and dried to prepare orange peel powder, the orange peel powder is mixed with distilled water, a hydrothermal reaction is carried out, the mixture is cooled to room temperature, and the mixture is filtered to obtain carbon quantum dots; the ratio of the orange peel powder to the distilled water is 0.5 g: 20-30 ml; the temperature of the hydrothermal reaction is 190-210° C., and the insulation time is 5-7 hours.

2. The preparation method according to claim 1, characterized in that: The drying temperature is 80-100° C. and the drying time is 2-3 days.

3. The preparation method according to claim 1, characterized in that: The filtration is carried out through a 0.22 μm microporous membrane.

4. Carbon quantum dots prepared by the method according to any one of claims 1 to 3 using orange peel as a carbon source.

5. The carbon quantum dots according to claim 4, characterized in that Its particle size is 2.2~6.2nm.

6. A method for detecting iron ions, characterized in that: The carbon quantum dots described in claim 4 or 5 are mixed with a solution containing iron ions, and after sufficient reaction, the fluorescence spectrum intensity is measured, and the concentration of the iron ions is calculated based on the change in the fluorescence spectrum intensity.

7. The method for detecting iron ions according to claim 6, characterized in that: The excitation wavelength of the fluorescence spectrum is 355-365 nm.

8. The method for detecting iron ions according to claim 6, characterized in that: The detection range of iron ions is 0~90μmol·L -1 .

9. A method for detecting L-ascorbic acid, characterized in that: The carbon quantum dots described in claim 4 or 5 are mixed with a solution containing iron ions, and after sufficient reaction, the fluorescence spectrum is measured. When the fluorescence is quenched, a solution containing L-ascorbic acid is added, and the fluorescence spectrum is measured again. The concentration of L-ascorbic acid is calculated based on the degree of recovery of the fluorescence intensity.

10. The method for detecting L-ascorbic acid according to claim 9, characterized in that: The detection range of L-ascorbic acid is 0~2000μmol·L -1 .

Citation Information

Patent Citations

  • Carbon quantum dot fluorescence labeling material with orange peels used as carbon source as well as preparation method and application of carbon quantum dot fluorescence labeling material

    CN104560035A

  • Nitrogen-doped fluorescent carbon quantum dot and preparation method and application thereof

    CN106753352A

  • Preparation of red fluorescent carbon nanodots, and method used for detecting ferric ions and ascorbic acid

    CN107043623A

  • Fluorescent carbon dot as well as preparation method and application thereof

    CN109054821A

  • Fluorescent nitrogen-and-sulfur-codoped carbon quantum dot, and one-step synthesis method and application thereof

    CN110257058A